2021
DOI: 10.1021/acs.jnatprod.1c00435
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Phenyl Amides from Hempseed on BACE 1, PPARγ, and PGC-1α in N2a-APP Cells

Abstract: In Alzheimer’s disease (AD) the accumulation of amyloid β (Aβ) plaques in the brain leads to neuroinflammation, neuronal cell dysfunction, and progressive memory loss. Therefore, blocking the formation of Aβ plaques has emerged as one of the most promising strategies to develop AD treatments. Hempseed is widely used as a food, and recently its compounds have shown beneficial effects on neuroinflammation. The objective of this study was to investigate whether a fraction rich in phenyl amide compounds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Taking into account previous reports that have discussed the possible neuroprotective activity of N-trans-feruloyltyramine through the stimulation of neurogenesis and neurotrophins, 34 in addition to the role of N-trans-caffeoyltyramine and N-transcoumaroyltyramine in the reduction of BACE1 gene expression, 6 our study results suggested the contribution of amide alkaloids as effective lead compounds for the development of AD therapies. Furthermore, the study reveals the benecial effects of B. indica and A. alopecuroides in the prevention as well as the potential treatment of neurodegenerative diseases owing to their phenyl amide contents.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Taking into account previous reports that have discussed the possible neuroprotective activity of N-trans-feruloyltyramine through the stimulation of neurogenesis and neurotrophins, 34 in addition to the role of N-trans-caffeoyltyramine and N-transcoumaroyltyramine in the reduction of BACE1 gene expression, 6 our study results suggested the contribution of amide alkaloids as effective lead compounds for the development of AD therapies. Furthermore, the study reveals the benecial effects of B. indica and A. alopecuroides in the prevention as well as the potential treatment of neurodegenerative diseases owing to their phenyl amide contents.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, bioactive compounds derived from plants have shown promising therapeutic activity in neurodegenerative diseases, making their evaluation as a source of alternative medicine for AD an effective approach. 6 Halophytes are plants with substantial economic potential and are potential sources of medication. 7 Several species of halophytes have been utilized in folk medicine for their ability to produce various bioactive compounds, such as terpenes, saponins, and alkaloids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathogenesis of AD is not completely clear, several hallmarks are associated with the pathological development of AD, including the abnormal accumulation of amyloid-β (Aβ) and tau protein, reactive oxygen species (ROS), and metal ions along with neuroinflammation. [8][9][10][11] Aβ is generated by the proteolysis of amyloid precursor protein (APP). The protein is first cleaved at its N-terminus by β-secretase (also called β-site APP cleavage enzyme1 (BACE1)), 12 and then the carboxy-terminal fragment (CTFβ) is cleaved by γ-secretase to form Aβ-peptide.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of AD is not completely clear, several hallmarks are associated with the pathological development of AD, including the abnormal accumulation of amyloid-β (Aβ) and tau protein, reactive oxygen species (ROS), and metal ions along with neuroinflammation. 8–11…”
Section: Introductionmentioning
confidence: 99%